Development and Validation of High Performance Thin Layer Chromatographic Method for the Estimation of Voglibose in Bulk and Tablet Dosage Forms: Estimation of Voglibose by HPTLC - Mallikharjuna Rao a , Nagasarapu; Ravikumar, K (Iranian Journal of Pharmaceutical Sciences, 2022)
A simple, fast, specific, precise, and accurate High-Performance Thin Layer Chromatographic method (HPTLC) was developed and validated for the estimation of Voglibose in bulk and pharmaceutical formulations. The chromatographic separation was carried out on precoated silica gel 60F254 aluminum plates using a mixture of acetonitrile: methanol: ammonia (15:4:0.1 % V/V/V) as mobile phase and densitometric evaluation of spots was carried out at 284 nm using Camag TLC scanner III with CATS 1.3.4 version software. The experimental parameters like band size of the spot application, chamber saturation time, solvent front migration, slit width, etc. were critically studied and optimum conditions were evolved. The drug was satisfactorily resolved with an Rf value of 0.66±0.03. The accuracy and repeatability of the proposed method were ascertained by evaluating various validation parameters like linearity (100 to 450 ng/spot), precision (intra-day % RSD 0.17 to 0.69, inter-day % RSD 0.20 to 0.29), accuracy (96.24±0.20), and specificity according to ICH guidelines. The limits of detection and quantification were 40ng/spot and 100 ng/spot respectively. HPTLC method provides a faster and cost-effective quantitative control for routine analysis of Voglibose in its formulation.